Diagnostic Capability of Next-Generation Sequencing Fusion Analysis in Identifying a Rare CASE of TRAF1-ALK-Associated Anaplastic Large Cell Lymphoma - Agarwal, Indu; Sabatini, Linda; Alikhan, Mir B. (Frontiers in Oncology, 2020)
Background: Anaplastic lymphoma kinase (ALK)-positive anaplastic large cell lymphoma (ALCL) is a rare T-cell neoplasm, accounting for approximately 3% of adult non-Hodgkin lymphomas. Although NPM1 is the most common fusion partner with ALK, many others have been described, necessitating break-apart FISH studies for confirmation of the diagnosis. TNF receptor-associated factor 1 (TRAF1) is a rare ALK partner that is thought to confer a worse prognosis in patients. We describe the utility of next-generation sequencing (NGS) RNA analysis in detection of this uncommon ALK partner. Case Description: A 42-year-old male with cervical lymphadenopathy presented for excisional biopsy. Following a tissue diagnosis of ALCL, ALK+, RNA from the biopsy was extracted from Formalin-fixed paraffin-embedded (FFPE) tissue and prepared for Anchored Multiplex PCR using the Archer® FusionPlex® v2 assay, which employs unidirectional gene-specific primers using NGS to detect novel or unknown gene partners. Results: Histologic evaluation of the excised lymph node showed atypical cells, including “horseshoe/kidney”-shaped nuclei. Neoplastic cells were immunoreactive against CD30, ALK (diffuse, cytoplasmic), CD2, CD4, granzyme B, and TIA-1. A diagnosis of ALCL, ALK+ was made. The pattern of ALK immunostaining suggested a non-NPM1-associated ALK translocation pattern, prompting further investigation. NGS fusion analysis showed a translocation involving exon 7 of TRAF1 and exon 20 of ALK. Conclusion: ALK positivity suggests an overall favorable prognosis of ALCL as compared to ALK-negative cases. However, in the rare published cases of TRAF1-ALK, an aggressive clinical course has been observed, which may reflect the aggressive propensity of this particular fusion, as these cases appear to be refractory to standard chemotherapy and also to the first generation ALK inhibitors. This study highlights the advantage of using NGS in RNA-based fusion assays to detect rare translocations, which can be of some clinical importance in detecting rare but aggressive fusion partners of ALK. As these technologies become more available, there is potential to identify such changes and effectively stratify the prognosis of ALCL patients.